Prácticas pedagógicas motivacionales en el proceso de enseñanza aprendizaje de los estudiantes de octavo, noveno y décimo grado de educación básica en el área de estudios sociales de la Unidad Educativa Carmen Mora de Encalada de la ciudad de Pasaje en el periodo lectivo 2014 - 2015. - Cojitambo Suárez, Boris Alexander (2015)
The development of this thesis entitled MOTIVATIONAL TEACHING PRACTICE IN THE TEACHING STUDENTS LEARNING EIGHTH, NINTH AND TENTH GRADE OF BASIC EDUCATION IN THE AREA OF SOCIAL STUDIES EDUCATION UNIT CARMEN MORA DE ENCALADA THE CITY OF PASAJE IN THE ACADEMIC YEAR 2014 - 2015 focuses on the study of motivational teaching practices in the teaching-learning process, due to the importance they represent in education.